Hubungan Tingkat Pengetahuan Deteksi Dini Kanker Payudara Terhadap Kepatuhan Pemeriksaan Payudara Sendiri (Sadari) Pada Remaja Putri Di MAN 2 Samarinda - Burhanto, Burhanto; Norwanda, Tri Putri Ayu (Akademi Kebidanan Bunga Husada Samarinda, 2024)
The aim of this study was to determine the relationship between the level of knowledge of early detection of breast cancer and compliance with breast self-examination in young women at MAN 2 Samarinda. The method used was quantitative with a cross-sectional approach and using the Chi Square test with a confidence level of 95% and alpha 5% (0.05). The results obtained were pValue equal to 0.000 less than α equal to 0.05, which means accepting the alternative hypothesis (Ha). The conclusion is that there is a relationship between the level of knowledge about early detection of breast cancer and compliance with breast self-examination (BSE) among young women at MAN 2 Samarinda